(untitled) (Damascus University Journal of agriculture sciences, 2021)
This study was carried out for Whole body extracts of virgin females of almond seed wasp which were analyzed by GC-MS to detect their components and to determine the sex pheromones. Infected almonds with almond seed wasp were collected from Al Fhaila – Homs in autumn (2015). The extraction on the females was carried out in Biological control studies and research center, and the analysis was accomplished in Faculty of science – Damascus university on march (2016). Results indicated the presence of two distinguish substances (alkadienes) were found in females and they are potential in the sex pheromone that secreted by female for mating process. Both compound contain two double bond at carbon 6 and 9 and both were (Z) isomere one has 23 carbons and the other has 25 carbons, so the two alkadienes were named (Z,Z)-6,9 tricosadiene and (Z,Z)-6,9 pentacosadiene. In addition to alkanes, alkenes and unknown substances which separated at different times through the total time 60 minutes.